Responding to user's expectation in the library : innovation Web 2.0 applications at JUIT Library : a case study - Ram, Shri (2011)
Article looks at the implementation of Web 2.0 applications at Jaypee University of Information Technology in India. Explores the expectations of users and their awareness and usage of the applications.